Program Serambi Islami Edisi Jum’at pada Sesi Teletilawah (Upaya Tvri untuk Meningkatkan Pengetahuan Membaca Alquran Secara Tartil Bagi Pemirsa) - Wulan Furrie (LUGAS Jurnal Komunikasi, 2017)
Quran is "the way of life" for Muslims. Reading Quran with tarteel is a must (Fardhu Ain). Therefore, TVRI as a public television that has a vision of educating the life of the nation contributed to invite audiences to improve their ability to read Quran with tarteel. This study aimed to determine what efforts made by TVRI to improve audiences’ knowledge in reading Quran with tarteel. Qualitative research method used in this study with in-depth interview. Informant in this study was a producer who has ideas to create programs TELETILAWAH Serambi Islami on Friday edition. The analysis used Theories of influences on Mass Media Content introduced by Pamela J Shoemaker and Stephen D. Reese. The results of this study found a large number of audiences’ attention to these programs and increased their awareness to read the Quran with tarteel.